Identification of single nucleotide polymorphisms (SNPs) in 5′ and 3′ untranslated regions (5′ UTR and 3′ UTR) of HSP70 gene in some Western Sudan indigenous cattle - Ismaeel, Fathi; Moussa , Mounir; Eltahir, Hamza A.; Shakam, Huda M. (Journal of Advanced Veterinary Research, 2024)
Heat shock proteins (HSPs) are a considerable family of evolutionarily conserved molecular chaperones that play an important role in protecting cells against cellular stressors. HSP70 is a sensitive, and superabundant gene associated with heat stress’s physiological adaptability. This research aimed to identify the polymorphisms in 5’ - 3’ untranslated regions (5’ UTR and 3′ UTR) of the HSP70 gene in western Sudan indigenous cattle. The genomic DNA was extracted from blood samples of Sudanese Red Fulani, Nyalawi, and Messeri cattle, and analyzed using the Sangar sequencing method. The results showed that the existence of 5 SNPs of g.802C>T, g.895C/-, g.1125A>C, g.1128G>T, and g.1204T>C at 5’ UTR and one SNP of g.64T>G at 3′ UTR. The moderate polymorphic informative content (PIC) and highest effective number of allele values were detected in SNP of g.895C/- (1.97) and g.64T>G (1.88) in Sudanese Red Fulani and indicated that these SNPs are highly polymorphic. The deletion of Cytosine (g.895C/-) and G (g.64T>G) alleles were the most frequent while the (–) and (GT) genotypes were the most frequent among these cattle. The chi-square (χ2) test revealed that the genotype frequency for the HSP70 gene disagreed with the Hardy–Weinberg equilibrium (p>0.05). This research is the first study concerned with HSP70 polymorphisms in Western Sudanese cattle. Thus, the results concluded that the HSP70 gene in (5’ UTR and 3′ UTR) in all studied cattle was polymorphic. The 2 SNPs of g.895C/- and g.64T>G are useful molecular markers to assist selection for thermal adaptation in Sudanese cattle breeds.